Quest for justice: Islamism, social justice, and civility in Islamic history. Issue 3 (2nd September 2018) - Milani, Milad; Cottle, Drew
ABSTRACT: This article examines Islamism as phenomenon and category in the context of the study of religion. It enquires about the experience of Islam in modernity at the juncture of Islam, justice, and civility in order to problematise the discourse on Islamism as political Islam. The argument is made that Islam is not a political religion, but a religion that has historically seen political power as part of its religious project. Further, that Islamism as a modern religio-political and socio-economic experience of Islam is inspired by contact between Islam and Marxism.